直驱型永磁同步风力发电机的全局最优参数辨识方法 (2024)
本发明公开了直驱型永磁同步风力发电机的全局最优参数辨识方法，步骤包括：初始化粒子群，给定系统噪声协方差阵Q和测量噪声协方差阵R的位置与速度初值；通过不断迭代找出问题的最佳解,更新Q值和R值；由适应度函数更新当前个体平均极值与群体极值；根据个体平均极值与群体极值进化停滞次数，并对极值进行扰动；通过测量更新与时间更新获得该时刻的系统状态最优辨识值。本发明能实现直驱型永磁同步风力发电机定子电阻、dq电感和永磁体磁链高精度辨识，具有速度快、泛化能力强的优点。 The invention discloses a global optimal parameter identification method of a direct-driven permanent magnet synchronous wind driven generator. The method comprises the following steps: initializing a particle swarm, giving a system noise covariance matrix Q, and measuring the position and speed initial value of a noise covariance matrix R; finding out an optimal solution of the problem through continuous iteration, and updating a Q value and an R value; updating a current individual average extremum and a group extremum by a fitness function; evolving stagnation times according to the individual average extremum and the group extremum, and disturbing the extremum; and obtaining the optimal identification value of the system state at the moment through measurement updating and time upd